Examining the Seasonal Correlations Among Different Ionospheric Indices During Solar Cycle Twenty-Four - Ezzat, Aula A.; Hadi, Khalid A. (Iraqi Journal of Science, 2024)
The present work aimed to examine the nature and degree of the cross-correlations among three different ionospheric indices: these are Optimum Working Frequency (OWF), Highest Probable Frequency (HPF), and Best Usable Frequency (BUF). VOCAP and ASASPS models were adopted to determine the datasets of the selected ionospheric indices. The determination was made for different transceiver stations that provide certain HF connection links during the minimum and maximum years of solar cycle 24, 2009 and 2014, respectively. Matlab program was implemented to produce the geodesic parameters for the selected transceiver stations. The determination was made for different path lengths (500, 1000, 1500, and 2000) Km and bearings (0o, 45o, 90o ........ 315o). Different correlation methods were used to examine the best determination coefficient values between the tested parameters. A third-order polynomial equation was set as the best correlation method that gave a better description for the correlation among the tested parameters. The proposed mathematical correlation equations were used to predict the seasonal values of the (HPF, OWF and BUF) parameters. The proposed equations were verified by comparing their values with the observed datasets during the study years. Also, the predicted values were tested using different statistical methods, which gave good results for all tested cases. يهدف العمل الحالي إلى دراسة طبيعة ودرجة الترابط بين ثلاثة مؤشرات آيونوسفيرية مختلفة وهي (HPF,OWF and BUF), تم استخدام نماذج VOCAP و ASASPS لحساب قيم البيانات للمؤشرات الآيونوسفيرية المختارة. اجريت الحسابات لمحطات الإرسال / الاستقبال المختلفة التي توفر روابط اتصال عالية التردد خلال سنوات الصغرى والعظمى للدورة الشمسية 24 (2009 و 2014) على التوالي. تم تنفيذ برنامج Matlab لايجاد قيم المعلمات الجيوديسية لمحطات الإرسال / الاستلام  لأطوال مسافات مختلفة (500، 1000، 1500 و 2000) كم واتجاهات مختلفة(0o, 45o, 90o ........ 315o). تم تطبيق طرق ارتباطية مختلفة لاختبار افضلها بين المعاملات المختبرة . تم اقتراح معادلات رياضية  متعددة الحدود (الدرجة الثالثة) كأفضل طريقة تصف القيم الارتباطية بين المعاملات المحددة لغرض الدراسة. تمكنت المعادلات المقترحة  من التنبؤ بالقيم الموسمية  للمؤشرات ((HPF و(OWF) و (BUF).و تم التحقق منها من خلال مقارنتها مع قيم المعلمات  المرصودة خلال سنوات الدراسة . كما تم اختبار القيم المتوقعة باستخدام طرق إحصائية مختلفة والتي قدمت نتائج جيدة لجميع الحالات المختبرة